Effects of weight training and water aerobics in pregnancy - Literature review (Research, Society and Development, 2021)
The present study, considering disinformation as one of the main causes of physical inactivity in pregnancy, analyzed the practice of activities such as resistance and strength training and aquatic exercise as alternatives to pregnant women. Aiming to understand the effects of weight training and water aerobics in pregnancy, assessing the benefits and risks of these practices for the woman and the fetus. Regarding the methodology, the study adopts the so-called literature review that used online databases to select articles published in the last 15 years, searched for the following keywords: Physical exercise in water; Pregnant; Resistance training; Aquatic exercises. The results showed that both practices can bring benefits to pregnant women and do not present risks, according to the majority of the authors found and cited. It is concluded that both practices can benefit the pregnant woman, being safe for the mother and fetus, without interfering in the gestational age, helping in weight control, reducing the symptoms of the gestational period. The choice must be made by the pregnant woman together with the Physical Education professional, considering the limitations and conditioning of the pregnant woman in order to delimit frequency and intensity of training.